Tổng hợp, đặc trưng và ứng dụng vật liệu nano-zeolit NaX từ cao lanh. I - Tổng hợp và đặc trưng vật liệu nano-zeolit từ cao lanh đã xử lý axit - Đôn, Tạ Ngọc; Anh, Hà Thị Lan; Bái, Trịnh Xuân; Vũ, Tô; Dương, Lê Văn (Vietnam Journal of Chemistry, 2012)
This paper presents the initial results of nano-zeolite NaX from acid treated kaolin with the present of organic template. Nano-zeolite NaX was characterized by XRD (SIEMENS D5005), SEM (JSM 5410 LV), TEM (TEM 1010), physical adsorption BET (Coulter SA3100). Synthesized nano-zeolite has high crystallinity, large surface area of 556 m2/g (external surface of 95 m2/g), and crystal size of 20 nm. Beside typical microspores, mesopores are formed from nano-size particles.